Bisnis UMKM di Era Digital : Pentingnya Literasi Keuangan di Kabupaten Banyumas - Faizal Rizky Yuttama; Budi Widadi (Indonesian Journal of Community Service and Innovation, 2025)
The development of digital technology is changing the business paradigm of micro, small and medium enterprises (MSMEs). Digital financial literacy is the key to optimizing the potential of technology, managing finances effectively, and protecting against the risks of online transactions. In the midst of intense competition, digital financial literacy helps strengthen customer trust and build loyalty through safe and efficient transaction experiences. Some common problems faced by small and medium enterprises in Banyumas Regency are lack of understanding and ability. Many smll and medium enterprises do not have sufficient knowledge or understanding of digital financial literacy. And security and privacy are issues for MSMEs when using digital financial solution. To overcome this problem, training was carried out for entrepreneurship development that focused on digital financial literacy. This program will increase the digital financial literacy of MSME stakeholders, optimize financial management, increase operational efficiency, and strengthen company sustainability in the digital era. The results of community service that have been carried out show that this activity has a positive impact on MSMEs, which is indicated by MSME actors using various digital financial applications to increase their working capital through digital financial financing patterns.